2018
DOI: 10.1016/j.ijantimicag.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes endocarditis: case report, review of the literature, and laboratory evaluation of potential novel antibiotic synergies

Abstract: Endocarditis is a rare but serious manifestation of Listeria monocytogenes (LM). However, the optimal treatment strategy for LM endocarditis has yet to be established. Current antibiotic strategies for listeriosis include penicillin G or ampicillin (AMP) monotherapy, or AMP + gentamicin combination therapy which is often favored for endocarditis. The primary objective of our investigation was to assess the utility of AMP + ceftriaxone (CRO) and AMP + daptomycin (DAP) against LM, modeling less nephrotoxic antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 18 publications
(24 reference statements)
2
25
0
Order By: Relevance
“…It is ubiquitous in nature with a broad host range. The bacterium has been isolated from soil, vegetation, and as part of the fecal flora in many mammals [1,[3][4][5][6]. It is also normally found in the stools of 1-5% healthy adults [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is ubiquitous in nature with a broad host range. The bacterium has been isolated from soil, vegetation, and as part of the fecal flora in many mammals [1,[3][4][5][6]. It is also normally found in the stools of 1-5% healthy adults [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…From 1968 to 2017, only 73 cases of listerial brain abscess were reported in the literature, with a case fatality rate of 27.3% [5]. Furthermore, endocarditis due to Listeria monocytogenes is a rare entity occurring in only about 5-8% of patients with listeriosis [2,4,13]. A review of the literature from 1955 to 2008 found only 68 case reports of listerial endocarditis [14], with a case fatality rate ranging from 37-50% [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations